Lessons from post-colonial Malaysian economic development - Jomo K. S.; Wee Chong Hui (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Malaysian economic development has been shaped by public policy in response to changing national and external conditions. Public investments peaked in the 1970s and early 1980s, until the policy reversals driven by sovereign debt concerns and new policy ideology fads. Foreign investments continued to be favoured after independence for ethnic political reasons. Thus, foreign investments continued to be very significant in financial services as well as manufacturing growth, both for import substitution from the 1960s and for export from the 1970s. Private investments were attracted by government provision of infrastructure, cheap but schooled labour, tax incentives, lax environmental regulations and an undervalued currency. Poverty reduction and ownership redistribution by ethnicity were most successful during the 1970s and early 1980s, although it is unclear how much these improved inter-ethnic relations. Economic liberalization and the growing influence of business interests and political elites have undermined the government's developmental role, culminating in the 1997-8 financial crisis and lacklustre growth since. Malaysian industrialization could only have been achieved with appropriate incentives for investments and technical progress through key policy interventions.
Keywords: O16; O2; 330; Malaysia; development strategies; liberalization; intervention